Multifaceted Bullying of Children with Disabilities: Challenges from Peers, Educators, and Parents - Chandra, Saumya (International Journal of Rehabilitation and Special Education (IJRSE), 2026)
Bullying remains a pervasive challenge in educational settings, disproportionately  affecting children with disabilities. This study explores the multifaceted nature  of bullying experienced by these children, examining the roles of peers, educators,  and parents in perpetuating or mitigating such behaviors. It incorporates informal  observations, qualitative interviews, and case studies to provide a comprehensive  understanding of the bullying dynamics. The findings highlight the prevalence of  bullying, including social exclusion, verbal abuse, and implicit bias from authority  figures. The study underscores the compounding effects of these experiences on the  emotional, cognitive, and social development of children with disabilities. The analysis  identifies systemic barriers within educational institutions that contribute to the  persistence of bullying, including inadequate teacher training, lack of inclusive policies,  and limited parental awareness. The study proposes evidence-based interventions,  structured peer support programs, educator sensitization workshops, and parental  engagement initiatives, to foster an inclusive and supportive environment for children  with disabilities. The research underscores the urgency of a multi-stakeholder  approach to effectively combat bullying and promote equity in educational settings.
Keywords: Bullying, Children with Disabilities, peer victimization, teacher discrimination, parental exclusion, inclusive education